The Efficacy of Workshop Model in Teaching Reading Comprehension - Paldy Paldy (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
This research is about the efficacy of workshop model in teaching reading comprehension. The aims of this research were to find out whether the use of workshop model is efficacious to improve the reading achievement of the sixth semester English department students of Universitas Cokroaminoto Palopo and to find out the students' interest toward application of workshop model in learning reading comprehension.